2021
DOI: 10.3389/fped.2021.685956
|View full text |Cite
|
Sign up to set email alerts
|

Modified Dual Hepatic Vein Anastomosis in Pediatric Living-Donor Liver Transplantation Using Left Lateral Segment Grafts With Two Wide Orifices

Abstract: Background: The anatomic variation of hepatic vein in the left lateral segment (LLS) increases the risk of outflow complication in pediatric living liver transplantation (LDLT). Here, we share a modified method for dual hepatic vein reconstruction in pediatric LDLT using LLS with two wide orifices.Methods: From Sep 2018 to Dec 2019, 434 pediatric LDLTs using LLS were performed in our center. Hepatic veins of grafts were classified into three types with emphasis on the number, size, and location of orifices at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The published study does not refer to a comparative analysis of the WIT, as well as the need and clamping time of IVC, with the other types of LLS grafts (control group) used. [26] In the current study, the HVG interposition technique showed no difference in WIT or the need for IVC clamping when compared with the other types of LLS grafts used. Another aspect of this discussion is the presence of a V3 in an extremely inferior location in the LLS graft, making it difficult or even impossible to directly anastomose this vein in the retrohepatic IVC, especially in small infants.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The published study does not refer to a comparative analysis of the WIT, as well as the need and clamping time of IVC, with the other types of LLS grafts (control group) used. [26] In the current study, the HVG interposition technique showed no difference in WIT or the need for IVC clamping when compared with the other types of LLS grafts used. Another aspect of this discussion is the presence of a V3 in an extremely inferior location in the LLS graft, making it difficult or even impossible to directly anastomose this vein in the retrohepatic IVC, especially in small infants.…”
Section: Discussionmentioning
confidence: 43%
“…[27] The large caliber formed by venoplasty between the HVG conduit and V2 allows a wide anastomosis; despite this, the higher GHV/RHV correlation in type IIIB LLS grafts did not determine the need for IVC clamping during implantation, as shown in Table 1. In the situation of extreme mismatching, this can be solved by communicating the 3 recipient's HV, with triangulation and enlargement of the common ostium toward the IVC, thus enabling the compatibility of the very small recipient Dar et al [28] HAG interposition a 3 HV venoplasty Case report 6 mo Patent graft HV Sakamoto et al [12] No BTVR−Dual HV anastomosis in recipient V2G: LHV + V3G: MHV or V2G: LHV/MHV + V3G: RHV 10 Median 7.9 y 1 HVOO (10%)-BV Hwang et al [8] HVG interposition b 3 HV venoplasty Case report 6 mo Patent graft HV Veerankutty et al [29] QVP anchored to V2G ± V3G Anteromedial IVC venotomy Case report 3 mo Patent graft HV Hou et al [26] No BTVR−Dual HV anastomosis in recipient V2G: LHV ± MHV V3G: Anteromedial IVC venotomy 08 Mean 15.6 mo…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Since then, different surgical venous anastomoses have been described. [15][16][17][18] A number of factors are known to affect the incidence of VOO after LLS graft transplantation including vessel size and length, number and anatomy of graft segmental veins, and graft positioning. 19 Of note, in the early postoperative period, VOO may be caused by technical problems; at a later stage, parenchyma growth, fibrosis, organized thrombus, and intimal hyperplasia play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…One such technique, initially described in 1991, involves the creation of a triangular anastomosis along the anterior surface of the inferior vena cava 14 . Since then, different surgical venous anastomoses have been described 15–18 …”
Section: Introductionmentioning
confidence: 99%